2016
DOI: 10.2134/jeq2015.09.0498
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Runoff Losses from Liquid Dairy Manure Applied 
with Low‐Disturbance Methods

Abstract: Manure applied to cropland is a source of phosphorus (P) and nitrogen (N) in surface runoff and can contribute to impairment of surface waters. Tillage immediately after application incorporates manure into the soil, which may reduce nutrient loss in runoff as well as N loss via NH volatilization. However, tillage also incorporates crop residue, which reduces surface cover and may increase erosion potential. We applied liquid dairy manure in a silage corn ( L.)-cereal rye ( L.) cover crop system in late Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…Surface broadcast application, whereby liquid manure (<6% total solids) is applied to the soil surface without incorporation into the soil, is the most common application method. Although it is less labor intensive than manure injection or tillage incorporation, runoff N and P loss risk is higher with broadcast manure application (Jokela, Coblentz, & Hoffman, 2012; Jokela, Sherman, & Cavadini, 2016; Maguire et al., 2011; Vadas et al., 2017; Williams, King, Ford, Buda, & Kennedy, 2016). In addition, liquid dairy manure has considerable ammonia N (NH 3 –N) that is subject to rapid loss to the atmosphere and deposition off‐site if manure is not incorporated or injected in to the soil (Apsimon, Kruse, & Bell, 1987; Sommer & Hutchings, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Surface broadcast application, whereby liquid manure (<6% total solids) is applied to the soil surface without incorporation into the soil, is the most common application method. Although it is less labor intensive than manure injection or tillage incorporation, runoff N and P loss risk is higher with broadcast manure application (Jokela, Coblentz, & Hoffman, 2012; Jokela, Sherman, & Cavadini, 2016; Maguire et al., 2011; Vadas et al., 2017; Williams, King, Ford, Buda, & Kennedy, 2016). In addition, liquid dairy manure has considerable ammonia N (NH 3 –N) that is subject to rapid loss to the atmosphere and deposition off‐site if manure is not incorporated or injected in to the soil (Apsimon, Kruse, & Bell, 1987; Sommer & Hutchings, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Strip‐till, aerator/band, and broadcast‐surf (mean, 42.8%) had a significantly larger fraction of large macroaggregates compared with fertilizer N plots (mean, 32.1%). Other studies have shown the beneficial effects of dairy manure on soil quality physical measures, including runoff potential (Jokela et al., 2009, 2016). In our study, manure treatments maintained higher total soil C and N and better soil structure as measured by MWD compared with fertilizer N treatments.…”
Section: Resultsmentioning
confidence: 98%
“…Nitrous oxide (N 2 O) is also a gaseous loss pathway for N, with fluxes tending to increase with incorporated manure (Chantigny et al., 2010; Sistani, Warren, Lovanh, Higgins, & Shearer, 2010). Because manure contains abundant N and phosphorus (P), field application and subsequent runoff/leaching can transport N and P in surface water runoff and leachate, posing a water quality risk (Eghball & Gilley, 1999; Jokela, Sherman, & Cavadini, 2016; Kovar, Moorman, Singer, Cambardella, & Tomer, 2011). Whether from manure or fertilizer, high N application rates increase N leaching risk to subsurface drainage and/or shallow groundwater (Al‐Kaisi & Licht, 2004; Dinnes et al., 2002; Halvorson, Wienhold, & Black, 2001; Sela et al., 2016; van Es et al., 2019; van Es, Sogbedji, & Schindelbeck, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia (NH 3 ) is considered a secondary GHG because a portion of N-containing fertilizers (particularly urea) can contribute to greater NH 3 fluxes compared with N sources incorporated into the soil (Dell et al, 2012;Duncan et al, 2017;Huijsmans et al, 2003;Powell et al, 2011;Sajeev et al, 2018;Webb et al, 2014;Wulf et al, 2002). Several studies have also demonstrated that incorporation of livestock manure not only conserves NH 3 but also substantially reduces surface runoff water N and phosphorus (P) loss risk in both corn and hay crop forage production fields (Jokela et al, 2012(Jokela et al, , 2016Sherman et al, 2020a). Soil moisture is an important factor affecting soil C and N transformations, including N 2 O fluxes related to changes in nitrification-denitrification reactions (Ball et al, 1999;Dalal et al, 2010;Gagnon et al, 2011;Kool et al, 2011;Liu et al, 2006;Perala et al, 2006;Thangarajan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%